SPECTRAL METHOD FOR SIMULATION OF VORTICITY-STREAMFUNCTION EQUATION WITH APPLICATION OF RAYLEIGH-BENARD CONVECTION - Artanta Ginting, Maria
In this nal project, we implement the spectral method to solve the vorticity - streamfunction equations. In spectral method functions are composed of periodic base functions: sinus and cosinus functions. Therefore this method is suitable for handling periodic problem. Here, we focus on two applications: the eect of external force and the eect of temperature dierence. In the rst application, we simulate the appearance of steady solution as response of the external force. Stability of this steady solution depends on the value of two dimensionless parameters: Reynolds number Re and experimental parameter . In the second application, we consider Rayleigh-Benard convection problem. In this problem, a horizontal layer of uid is heated from below, and as a result the uid develops a regular pattern of the convection cells known as Benard cells. By applying the spectral method to the corresponding equations, we simulate the appearance of this cells.